Modification of rambutan (Nephelium lappaceum L.) seed fat by chemical interesterification to produce vanaspati-like fat - Ghobakhlou, Fatemeh (2019)
The rambutan (Nephelium lappaceum L.) is a common and popular fruit grown in Malaysia. The flesh is processed industrially to produce juices, jams, jellies and marmalade, while the seed is considered as an agro-industrial waste. A novel way to reduce the wastage is to use rambutan seed as alternative natural source of edible fat with possible food applications as it has been reported that the seed possesses a relatively high proportion of fat (between 14% and 41%). Hence, the goals of this study were to characterize the physicochemical properties of fat from the seeds of three varieties of locally grown rambutan (R4, 47 and Serjan) and select the best variety as the source of fat to optimize the chemical interesterification reaction between rambutan seed fat and palm stearin. From the reaction, the best interesterified fat blend was selected for development of a vanaspati-like fat which was then evaluated and compared with commercial vanaspati during three months of storage period at 25 ˚C. Results obtained showed that there was a significant difference (p < 0.05) between the crude fat content (34.25-37.62%), iodine value (44.26-47.49 g I2 /100g oil) and melting point (24.54-26.60 ˚C) among the three varieties. Variety R7 was chosen to be subjected to chemical interesterification process as its seed contained the highest (p < 0.05) crude fat content (37.62 %). Response surface methodology (RSM) was employed based on a five-level, threefactor central composite design (CCD) to optimize the chemical interesterification conditions to produce a vanaspati-like fat with the desired solid fat content (SFC). In this study, rambutan seed fat (RSF) was blended with palm stearin (PS). The effect of three factors namely rambutan seed fat ratio (50-100 w/w), reaction temperature (60–90 ˚C) and reaction time (30–60 min) on responses such as SFC at 20 ˚C, 25 ˚C, 30 ˚C and 35 ˚C were investigated. The response optimizer plot suggested that rambutan seed fat ratio, reaction temperature and time should be 60 w/w, 66 ˚C and 30 min, respectively, to produce a vanaspati-like fat with optimal SFC. Interesterification significantly (p < 0.05) increased the free fatty acid content and reduced melting point and SFC of blends. The physicochemical and textural properties of experimental vanaspati (EV) prepared from chemically interesterified RSF:PS (60:40) blend at 66 ˚C for 30 min and commercial vanaspati (CV) throughout three months of storage at 25 ˚C were evaluated and compared. Both EV and CV had significant (p < 0.05) increments in peroxide value (PV), p-anisidine value (p -AV), solid fat content and hardness throughout storage. PV of the EV and CV after three months of storage were within acceptable levels of 2.23 and 2.52 meq O2/kg, respectively. The initial p -AV of EV was found to be 0.84 and for CV it was 1.2, and after storage period of three months, there was a 205.9% and 206.6% increase, respectively. The thermal behavior of EV and CV remained unchanged during storage. The β crystal form became predominant in EV and CV after 4 and 6 weeks of storage, respectively. It was observed that post-hardening occurred in both experimental and commercial vanaspati during storage. In general, the study successfully showed that rambutan seed fat may be used to produce a vanaspati-like fat when interesterified with palm stearin. Vanaspati produced from the blend undergo some physico-chemical changes, similar to changes that occurred when commercial vanaspati was stored under similar conditions.